南极深海底泥色盐杆菌属NJS-2 ectABC基因克隆及二氨基丁酸转氨酶ectA基因的表达 - 傅英楠; 陈志亮; 姜蔚宇; 陈荣忠 (2007)
从南极深海底泥中分离筛选得到一株中性嗜盐菌Chromhalobacter sp.NJS-2,以该菌株基因组为模板,利用PCR技术扩增出ectABC基因,基因全序列大小为2378bp。OMIGA软件分析该基因序列上含有三个阅读框,大小分别为576bp、1272bp和393bp,预测其分别编码二氨基丁酸乙酰转移酶(EctA)、二氨基丁乙酸转氨酶(EctB)和四氢嘧啶合酶(EctC)。将二氨基丁酸乙酰转移酶ectA基因的PCR扩增产物克隆至表达载体pET-his,构建重组表达载体pET-his-ectA,并经酶切、PCR鉴定和测序验证,结果表明其目的基因的插入位置、大小和读码框均正确。SDS-PAGE分析,出现大小约21kDa的目的蛋白条带。 Chromhalobacter sp.NJS-2 was isolated from Antarctica deep-sea sediment.The ectABC gene from this strain was amplified by PCR,consisting of 2378bp.Analysis of the OMIGA software showed that the whole sequence involves three open reading fragments,which were 576bp、1272bp and 393bp.The three open reading fragments encoded L-diaminobutyric acid transaminase(EctB),L-diaminobutyric acid acetyl transferase(EctA),and ectoine synthase(EctC),respectively.The amplified fragment of ectA was cloned into the expression vector pET-his.The insert position,the size and the reading frame were identified by PCR,restriction digestion and the sequence analysis of the recombinant plasmids.SDS-PAGE showed that the relative molecular mass of the expression product was 21kDa as predicted,which indicated that the recombinant plasmids could express the gene of L-diaminobutyric acid acetyl transferase.Enzyme activity detection of purified EctA partially elucidated the biosynthetic pathway of ectoine. 国家大洋专项(DY105-04-02-06)